Association of plasma homocysteine with cognitive impairment in patients with Parkinson’s disease - Yan Xiao; Lin-Hua Gan; Xiao-Niu Liang; Zhi-Heng Xu; Tian-Yu Hu; Xiu-Yuan Li; Yi-Lin Tang; Jian Wang; Yi-Qi Liu (Frontiers in Aging Neuroscience)
BackgroundElevated plasma homocysteine (Hcy) has been reported as a risk factor for cognitive impairment in the general population. However, there are conflicting results regarding the relationship between Hcy and cognitive impairment across various cognitive domains in Parkinson’s disease (PD).ObjectiveThis study aims to explore the association between plasma Hcy levels, cognitive impairment, and dysfunction in various cognitive domains among PD patients with and without mild cognitive impairment (MCI).MethodsA total of 101 PD patients underwent plasma Hcy measurement, comprising 50 PD-MCI patients and 51 patients with normal cognition (PD-NC). A battery of neuropsychological tests was administered to assess different cognitive domains. Adjusted generalized linear models were used to assess the correlations between Hcy levels and cognitive functions.ResultsAs anticipated, PD-MCI patients demonstrated a significant decline in cognitive function across all five cognitive domains (memory, executive function, attention/working memory, language, and visuospatial function). Elevated plasma Hcy levels (≥ 10 μmol/L) were associated with a higher odds of PD-MCI, even within the normal range of Hcy levels (< 15 μmol/L). After adjusting for confounding factors, a negative correlation was observed between plasma Hcy levels and the performance on specific cognitive tests evaluating executive functions in PD, such as the Stroop Color-Word Test-C (β = −1.123, 95% CI = −1.845 ∼−0.401, p = 0.0023).ConclusionThis study underscores a significant link between plasma Hcy levels and PD-MCI, particularly concerning executive dysfunction, even within the normal range of Hcy levels (< 15 μmol/L).